Assesment Entrepreneurship Skills Literacy For Post Graduate Student's - Khomsatun Ni'mah; Krisna Sujaya; Anita Eka Putri (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
The success of the implementation of the Vision of the Master of Mathematics Education Study Program which is to produce graduates who are superior, nationally minded, and entrepreneurial can be identified using an instrument. One of the keywords in the Vision is graduates who have an entrepreneurial spirit. Developing an instrument to identify the Vision of the Study Program is an important thing to do. The research method used is development research (R&D) using the ADDIE model. The results of the field trial of research on 31 students showed that the average achievement of group skills was better than personal skills, but smaller than interpersonal skills. The results of expert validation stated that AESL was feasible to use with improvements. The results of the user response questionnaire stated that AESL was categorized as very good.